EKSISTENSI DAN REFORMASI HUKUM KELURGA ISLAM DI INGGRIS - Mutmainnah; Rahmawati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
this paper discusses the existence of family law in the UK which began to be looked at by the government since 2018, with a legal case experienced by one of the immigrants, the British government for the first time recognized the existence of Islamic law. Although the majority of Islamic law in force is still subject to the existing positive legal rules, but this is a special thanksgiving for the Muslim minority in Britain, because since 1970 they want to apply Islamic law to themselves in the country but have always been rejected by the British government, along with increasing their population, it is not impossible to see Britain as a moderate country in this regard. appeal case filed in February 2020 by one of the immigrants related to the problem of his family made Britain begin to pay attention to Muslim minorities, there are even researchers who concluded specifically the English marriage law it is time for reform to cover all the needs of its people